Hooligan art and high-risk collectors: Charles Saatchi, Young British Art and the origins of the »collector’s artist«: Vom Ausstellungskünstler zum Sammlerkünstler - Grebe, Anja (Austrian Journal of Historical Studies, 2006)
The article investigates the role of the collector and his impact on the artists, the art market and the modern art system in general. Due to this influence, we can witness the emergence of a new type of artist, the »collectors artist«. In contrast to the modern »exhibition artist« the »collectors artist« works for one main collector under who’s name his work is then presented to the public. The strategies of both artists and collectors are analysed on the basis of the relationship of the British »supercollector« Charles Saatchi and the group of the Young British Artists. The article examines the background of the success story of the so-called »Saatchi-garde« which is strongly related to the role of Charles Saatchi acting as collector, promoter, exhibition organiser and art dealer at the same time.